Optimalisasi Metode Karyawisata untuk Pemahaman Keragaman Sosial Budaya Siswa Sekolah Dasar - Risalah Nur Ashfiya; Ibnu Muthi (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to examine the optimization of the field trip method in improving elementary school students' understanding of social and cultural diversity. The background of this study is based on the need for a learning approach that is not only informative, but also contextual and participatory, considering the importance of instilling the values ​​of tolerance and multiculturalism from an early age. This study uses a descriptive qualitative method based on literature studies, by reviewing various sources of literature such as journal articles, academic books, and relevant digital documents. The results of the study show that the field trip method makes a significant contribution to contextual learning, especially in socio-cultural material. This activity encourages students to experience diversity in society firsthand, develop empathy, tolerance, and strengthen 21st century skills such as critical thinking, collaboration, and communication. However, optimizing this method requires systematic planning, support from various parties, and innovation in integrating technology and project-based approaches. Therefore, the field trip method has great potential if applied in a structured manner in the learning process in elementary schools. This study recommends that schools and teachers actively develop field trip programs that are integrated with the curriculum and based on real experiences.